2009
DOI: 10.1016/j.ejphar.2009.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The flavonoid dioclein is a selective inhibitor of cyclic nucleotide phosphodiesterase type 1 (PDE1) and a cGMP-dependent protein kinase (PKG) vasorelaxant in human vascular tissue

Abstract: The inhibitory effect of the flavonoid dioclein was assessed on purified vascular cyclic nucleotide phosphodiesterase isoforms (EC 3.1.4.17, PDE1-5) in comparison with 8-methoxymethyl-isobutylmethylxanthine (8-MM-IBMX) and vinpocetine which are currently used as PDE1 inhibitors. The mechanism underlying the vasorelaxant effect of dioclein was investigated in human saphenous vein. Dioclein inhibited PDE1 more selectively than vinpocetine and 8-MM-IBMX, with IC(50) values of 2.47+/-0.26 and 1.44+/-0.35 microM, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…PDE1 protein expression was previously described in cultured aorta SMCs isolated from several species including rat [17], but PDE1 hydrolyzing cAMP activity was essentially shown in cells from other species [17], [31], [32]. Increasing MIMX concentration to 50 µM further increased the inhibitory effect of MIMX when used alone, but had no additive effect in the presence of PDE3 and PDE4 inhibitors suggesting that increasing MIMX concentration induces non-selective inhibition, probably towards PDE3 or PDE4, according to its affinity values [25], [27]. Finally, we confirmed the absence of PDE2 expression and activity in our conditions, as shown in previous works [33].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…PDE1 protein expression was previously described in cultured aorta SMCs isolated from several species including rat [17], but PDE1 hydrolyzing cAMP activity was essentially shown in cells from other species [17], [31], [32]. Increasing MIMX concentration to 50 µM further increased the inhibitory effect of MIMX when used alone, but had no additive effect in the presence of PDE3 and PDE4 inhibitors suggesting that increasing MIMX concentration induces non-selective inhibition, probably towards PDE3 or PDE4, according to its affinity values [25], [27]. Finally, we confirmed the absence of PDE2 expression and activity in our conditions, as shown in previous works [33].…”
Section: Discussionmentioning
confidence: 90%
“…Cil (1 µM, a selective PDE3 inhibitor [24]) and Ro (10 µM, a selective PDE4 inhibitor [25]) reduced cAMP-PDE activity by 20% and 40%, respectively. As no perfect PDE1 inhibitor is commercially available, we used MIMX which blocks PDE1 activity by interfering with its catalytic site with a low micromolar affinity and exhibits a selectivity over other PDEs of 30- to 50-fold [25]-[27]. MIMX decreased cAMP-PDE activity by 22% and 37%, when used at 10 µM and 50 µM, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, no involvement of PDE1A or any other PDE1 variants in the anti‐proliferative effect of vinpocetine were investigated in their study 56. But, it should be noticed that vinpocetine is a poor PDE1 inhibitor 57 and not specific for PDEs since it also activates Ca 2+ ‐activated K + channel (BK Ca ) in opposite to 8‐bromo cGMP that is ineffective 58.…”
Section: Discussionmentioning
confidence: 99%
“…Flavanone as a subclass of flavonoids consist of a large group of naturally existing polyphenolic compounds widely distributed in plants [22,23]. Previous studies have demonstrated that some flavonones, such as hesperetin and naringenin present relaxation effects on the rat aorta [2426]. Farrerol, a typical natural flavanone, has been isolated from Rhododendron dauricum L., and has been extensively used to alleviate symptoms associated with bronchial asthma in China [27].…”
Section: Introductionmentioning
confidence: 99%